Teacher Development and Teacher Education in Developing Countries On Becoming and Being a Teacher - Bashiruddin, Ayesha (Palgrave Macmillan UK, 2018)
This book contributes to understanding of how individual teachers in developing countries grow and evolve throughout their careers. Based on the analysis of 150 autobiographies of teachers from a range of regions in the developing world including Central Asia, South Asia, East Africa and the Middle East, the author celebrates individual teachers' voices and explores their narratives. What can these narratives tell us about 'becoming' and 'being' a teacher, and the process of teacher development? What is different about 'becoming' and 'being' a teacher in the developing world? By analysing the distinct narratives, the author explores these central questions and discusses the implications for further teacher development and education in these regions. In doing so, she transforms teachers' embodied knowledge into public knowledge, shining a light onto the challenges they face in the Global South and exploring how research can be advanced in the future. This uniquely researched book will be of interest and value to students and scholars of education in the developing world. .